횡격막 탈장의 외과적 고찰 - 허강배; 하현철; 김창수; 이재성; 조성래; 김송명 (Taehan Hyungbu Oekwa Hakhoe chi, 1993)
Fourteen cases of diaphragmatic hernias surgically treated at the Dept. of Thoracic ＆ Cardiovascular Surgery in Kosin Medical Center from Jan. 1979 to Feb. 1991, were reviewed in this study. This report includ 9 cases of traumatic diaphragmatic hernia, 5 cases of congenital diaphragmatic hernia. Among the traumatic hernias, 5 cases were blunt trauma and 4 cases were penetrating trauma. Five cases of congenital diaphragmatic hernias were presented, including 2 cases of esophageal hiatal hernia, 2 cases of Bochdalek's hernia and a case of Morgagni's hernia. Operation was performed in all patients. Results of all treated cases were excellent.